2017
DOI: 10.1002/ejhf.788
|View full text |Cite
|
Sign up to set email alerts
|

What proportion of patients with chronic heart failure are eligible for sacubitril–valsartan?

Abstract: Of patients with HFrEF referred to a clinic such as ours, only 21% fulfilled the PARADIGM-HF randomization criteria, on which the ESC Guidelines are based; this proportion rises to 60% if background medication is ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 25 publications
7
73
0
4
Order By: Relevance
“…Similar results were shown in a previous study, where 7% of the total heart failure population in a single‐centre setting fulfilled the PARADIGM‐HF criteria 20. This highlights the need for studies in heart failure with ejection fraction > 40%.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were shown in a previous study, where 7% of the total heart failure population in a single‐centre setting fulfilled the PARADIGM‐HF criteria 20. This highlights the need for studies in heart failure with ejection fraction > 40%.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, NYHA functional class presents difficulty for use as a criterion on which to base eligibility for treatment with sacubitril/valsartan. Therefore, we had conducted a sensitivity analysis in which we considered those with missing EF and NYHA class data and missing NYHA class data only eligible for sacubitril/valsartan, and in this scenario, our eligibility rate rose to 37–46%, a similar rate as that reported earlier …”
Section: Discussionsupporting
confidence: 54%
“…We found that nearly one in three patients with HFrEF at the VAGLAHS was eligible for treatment with sacubitril/valsartan. It has been estimated that if the criteria from the PARADIGM‐HF trial are strictly followed, then sacubitril/valsartan should be prescribed to < 25% of patients with HFrEF . Researchers found that 12% of patients in a community HF clinic in the United Kingdom were eligible for sacubitril/valsartan treatment using the PARADIGM‐HF trial criteria .…”
Section: Discussionmentioning
confidence: 99%
“…This agent is now licenced for use in certain well‐defined circumstances . However, as is always the case with novel therapeutic strategies, there is a need to look closely at how this agent performs in the routine community HF‐rEF population, who are likely to be older, more frail, and have increased burden of comorbidities . This ‘community testing' of a new compound may be of particular importance with sacubitril‐valsartan, given its widespread biological effects on various neuroendocrine and signalling systems, potentially affecting these to different degrees in community patients compared with clinical trial patients.…”
Section: Introductionmentioning
confidence: 99%